2002
DOI: 10.9795/bullgsj.53.573
|View full text |Cite
|
Sign up to set email alerts
|

Bouguer Gravity Anomalies in the Fukuoka area, Kyushu,Japan.

Abstract: Abstract:A new gravity map of the Fukuoka district was published. It is a map of the 1:200,000 gravity map series by the Geological Survey of Japan, AIST. The gravity data were compiled from 11,937 stations including 1,513 new stations. These new gravity surveys were carried out around the Fukuoka area. We show the table with gravity data for 706 new stations around the central part of the Fukuoka City area. This Bouguer gravity anomaly map with an assumed density of 2.3 g/cm 3 clearly revealed the structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The high-V p region is found just east of the earthquake fault. The Bouguer gravity anomaly in this region, which was reported by Morijiri et al (2002) and AIST (2005), shows a similarity to the spatial pattern of velocity perturbation. In the present study, the low-density anomaly corresponds to the low-velocity region, while.…”
Section: Discussion and Summarysupporting
confidence: 79%
“…The high-V p region is found just east of the earthquake fault. The Bouguer gravity anomaly in this region, which was reported by Morijiri et al (2002) and AIST (2005), shows a similarity to the spatial pattern of velocity perturbation. In the present study, the low-density anomaly corresponds to the low-velocity region, while.…”
Section: Discussion and Summarysupporting
confidence: 79%
“…Gravity data newly supplemented (a) for western Japan: 649 land gravity data taken from Morijiri et al [2002] and 924 marine data taken from Koizumi et al [1994], and (b) for Hokkaido: 5284 land gravity data provided by A. Yamamoto of Hokkaido University and 614 taken from Morijiri et al [2000].…”
Section: Supplementation Of Gravity Data In Gapsmentioning
confidence: 99%
“…Newer survey results have been reported in tabular form in their bulletins. We compiled two sets of point gravity data on land: 649 data for Fukuoka from Morijiri et al [2002], as shown in Figure 3a, and 614 data for eastern Hokkaido from Morijiri et al [2000], as shown in Figure 3b.…”
Section: Supplementation Of Gravity Data In Gapsmentioning
confidence: 99%